Changes in soil microbial metabolic activity following long‐term forest succession on the central Loess Plateau, China - Liu, Yulin; Song, Xinzhang; Wang, Kaibo; He, Zhirui; Pan, Yingjie; Li, Jiwei; Hai, Xuying; Dong, Lingbo; Shangguan, Zhouping; Deng, Lei (Land degradation & development, 2023)
Forest succession can alter terrestrial ecosystem processes and potentially impact subsurface carbon dynamics. However, the effects of long‐term forest succession on soil microbial metabolic activity remain unclear. This study investigated a long‐term forest succession approximately ~160 years after farmland abandonment on the central Loess Plateau, China, to explore the changes in soil microbial metabolism following the forest succession. Among them, the soil basal respiration (BR), microbial quotient (qMB), and metabolic quotient (qCO2) were studied. The results showed that the BR and qCO2 were increased following forest succession, whereas the qMB showed the opposite trend. Forest succession also increased the activities of β‐1,4‐glucosidase (BG) and β‐D‐cellobiosidase (CBH). The increase of BR and qCO2 and the decrease of qMB occurred in the early stage (<60 years). However, the increase of BG and CBH mainly occurred in the later period (>100 years). Soil microbial metabolic activity was closely related to litter biomass, dissolved organic carbon, fungal, and bacterial community composition. In conclusion, long‐term forest succession changes soil microbial community structure and promotes soil organic carbon accumulation, while the increase of soil respiration and metabolism promotes the release of carbon element following forest succession, thus reducing soil microbial carbon utilization efficiency.